Faktor risiko kejadian diare pada anak balita (12-59 bulan) di Puskesmas â€œXâ€ Kota Jambi - Hendra Dhermawan Sitanggang; Inas Tri Ramadhanti; RD Halim (Riset Informasi Kesehatan, 2022)
Background: Diarrhea is the second major contributor to morbidity and mortality of toddlers in various countries, including Indonesia. Diarrhea in toddlers has also occurred in Jambi Province. In 2019, Tahtul Yaman Primary Health Care was one of the Primary Health Care in Jambi City with the highest incidence of diarrhea. The study aimed to determine the risk factors associated with diarrhea in toddlers (12-59 months) in Tahtul Yaman Primary Health Care in Jambi City. Methods: The study used a case-control study design with 70 participants, consist of 35 cases and 35 controls taken by quota sampling. The dependent variable in this study was the incidence of diarrhea, and the independent variables were food sanitation, exclusive breastfeeding, vitamin A, Complete Basic Immunization, type of water source, and toilet facilities. Data were analyzed using a chi-square test for bivariate and regression logistic for multivariate analysis. Results: The multivariate analysis showed that relationship between food sanitation (OR=3,591; 95% CI=1,186-10,877), complete immunization status (OR=4,110; 95% CI=1,281-13,182), and toilet facilities (OR=6,051; 95% CI=1,291-28,365) with diarrhea. While factors unassociated were exclusive breastfeeding (OR=1,324, 95% CI=0,467-3,750), vitamin A (OR=1,477, 95% CI=0,541-4,032), type of water source (OR=1,304, 95% CI=0,474-3,590 ). Conclusion: Food sanitation, complete immunization status, and toilet facilities as risk factors for the incidence of diarrhea. A dominant factor that affected the incidence of diarrhea in children aged 0-59 months was the toilet facilities.